2022 44th Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2022
DOI: 10.1109/embc48229.2022.9871656
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Method for Full-Inversion-Based Ultrasound Elastography of the Liver

Abstract: Similar to many other types of cancer, liver cancer is associated with biological changes that lead to tissue stiffening. An effective imaging technique that can be used for liver cancer detection through visualizing tissue stiffness is ultrasound elastography. In this thesis, we show the effectiveness of an enhanced method of tissue motion tracking used in quasi-static ultrasound elastography for liver cancer assessment compared to other state of the art methods. The method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Conventional ultrasound has always been the first choice for the clinical screening of liver cancer, and can effectively visualize the size, number, position, internal echo and other parameters, in liver cancer lesions. However, ultrasound can be affected by a range of factors, including acoustic window, gas, body position and angle; thus, conventional ultrasound is of limited value for the diagnosis of liver cancer [12,13]. Research has shown that CEUS can comprehensively and objectively reflect blood perfusion in new vessels and micro-vessels within tumors, thus improving the clinical diagnosis of liver cancer [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional ultrasound has always been the first choice for the clinical screening of liver cancer, and can effectively visualize the size, number, position, internal echo and other parameters, in liver cancer lesions. However, ultrasound can be affected by a range of factors, including acoustic window, gas, body position and angle; thus, conventional ultrasound is of limited value for the diagnosis of liver cancer [12,13]. Research has shown that CEUS can comprehensively and objectively reflect blood perfusion in new vessels and micro-vessels within tumors, thus improving the clinical diagnosis of liver cancer [14][15][16].…”
Section: Discussionmentioning
confidence: 99%